"I'd like to be that attractive, but at least I'm smart": How exposure to ideal advertising models motivates improved decision‐making. Issue 4 (3rd April 2014) - Sobol, Kamila; Darke, Peter R.
Abstract: The use of idealized advertising models has been heavily criticized in recent years. Existing research typically adopts a social comparison framework and shows that upward comparisons with models can lower self‐esteem and affect, as well as produce maladaptive behavior. However, the alternative possibility that consumers can cope with threatening advertising models by excelling in other behavioral domains has not been examined. The present research draws on fluid compensation theory (Tesser, 2000) and shows that idealized models motivate improved performance in consumer domains that fall outside that of the original comparison. These more positive coping effects operate through self‐discrepancies induced by idealized models, rather than self‐esteem or negative affect. Specifically, self‐discrepancies motivate consumers to improve decision‐making by: 1) making more optimal choices from well‐specified consideration sets, and 2) better self‐regulating indulgent choices. More broadly, the current research integrates and extends theories of fluid compensation and self‐discrepancy, as well as provides a more complete picture of the ways in which consumers cope with idealized advertising models.